The effectiveness of short film to reduce students bullying behavior in junior high school - Kholida, Khafani Maya; Setiawan, Antonius Ian Bayu; Purnama, Diana Septi (Universitas Negeri Padang, 2023)
The phenomenon of bullying behavior is behavior that is very close to students. Prevention of bullying is one of the tasks of guidance and counseling teachers through classical guidance services. One of the media that can be used by guidance and counseling teachers is a short movie. This study aims to determine the effectiveness of short movie to reduce bullying behavior. This research is quantitative research with experimental methods. The research design uses a one-group design with a random sampling subjects. There are 36 subjects for class VIII junior high school students in Sleman. Researchers distributed anti-bullying questionnaires for the pre-test and post-test and analyzed them using the T test. The result is an increased understanding of bullying behavior in students after watching a short movie, so the use of a short movie is considered effective to reduce bullying behavior because of the influence of vicarious learning theory. Based on the results of the T-test, there is a 30.200 difference in the pretest and posttest scores, which indicates effectiveness. The N-Gain test results also yielded a score of 63%, which is in the quite effective category.